2006
DOI: 10.1016/j.neuron.2006.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Subplate Neurons Regulate Maturation of Cortical Inhibition and Outcome of Ocular Dominance Plasticity

Abstract: Synaptic plasticity during critical periods of development requires intact inhibitory circuitry. We report that subplate neurons are needed both for maturation of inhibition and for the proper sign of ocular dominance (OD) plasticity. Removal of subplate neurons prevents the developmental upregulation of genes involved in mature, fast GABAergic transmission in cortical layer 4, including GABA receptor subunits and KCC2, and thus prevents the switch to a hyperpolarizing effect of GABA. To understand the implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
228
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(234 citation statements)
references
References 64 publications
6
228
0
Order By: Relevance
“…The advent of retrograde tracing techniques and intracellular dye injections revealed that, as a general rule, neurons in the upper layers 2 and 3 tend to form corticocortical connections, including projections to the contralateral hemisphere across the corpus callosum, whereas neurons in layers 5,6, and the subplate are the source of subcortical projections to targets that include the spinal cord, pons, midbrain, and thalamus. Neurons in layers 1 and 4 extend axons locally within the cortex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of retrograde tracing techniques and intracellular dye injections revealed that, as a general rule, neurons in the upper layers 2 and 3 tend to form corticocortical connections, including projections to the contralateral hemisphere across the corpus callosum, whereas neurons in layers 5,6, and the subplate are the source of subcortical projections to targets that include the spinal cord, pons, midbrain, and thalamus. Neurons in layers 1 and 4 extend axons locally within the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…The upper preplate, which is known during development as the marginal zone, is populated by Cajal-Retzius neurons, of which many or most are derived from a region known as the cortical hem (located near the hippocampal anlage) and then migrate tangentially to populated the neocortex [4,5]. The deeper domain of the preplate becomes the subplate, a largely transient zone of neurons that plays important roles in axon targeting during development [6]. Within the cortical plate, neurons of the deepest layers (6 and 5) are generated at the earliest stages, followed by neurons of layers 4, 3 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…OD ratio was computed as contra/ipsi VEP amplitude ratio. OD plasticity experiments using Arc and qRT-PCR were carried out as described (11,(29)(30)(31)48). ANOVA, t test, or Wilcoxon was used for statistical comparisons, and P < 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Because SNs have been implicated in circuit assembly (8,9), it would be interesting to perform diphtheria toxin-mediated ablation of RMTW cells and assess how this manipulation affects the assembly of cortical cytoarchitecture. The report by Pedraza et al (11) provides a significant advancement to our current knowledge of early neuronal subtype diversity and paves the way to ask further fundamental questions in an effort to unravel the logic underlying wiring of the brain.…”
Section: Future Directionsmentioning
confidence: 99%
“…Remarkably, the dorsolateral geniculate nucleus becomes uncoupled from the visual cortex upon SN ablation, resulting in marked impairment of sensory information processing (8). In addition to a role in the maturation of glutamatergic activity, SNs regulate the maturation of GABAergic innervation by controlling the expression of the chloride cotransporter KCC2 (9). Finally, SNs have been implicated in regulating the proper assembly of cortical columns (10).…”
mentioning
confidence: 99%